"The Stuff You Need Out Here": A Semiotic Case Study Analysis of an Agricultural Company's Advertisements - Emily B. Rhoades; Tracy Irani (Journal of Applied Communications, 2008)
In today’s mediated society, people are continually searching to describe relationships among themselves, the items they encounter in their physical environment, and the cultural and historical contexts in which they reside. By placing meaning-laden visuals in a medium as popular as magazines with rural audiences, advertisers are sending messages as to what rural life is. The 2004-2005 advertising campaign of the Tractor Supply Company utilized photographs of rural life to sell viewers “ The stuff you need out here.” This advertising campaign, which relied heavily on a humorous appeal to play into stereotypical images of rural life, was seen in a variety of magazines that reach rural audiences. Using semiology as the framework of how images construct meanings, this case study sheds light on the various messages behind these advertisements and how they convey the cultures of rural life to farm and non-farm audiences. It is apparent that these advertisements have a tendency to play into the dominant ideology of what farming and farmers look like. Through simplistic images playing into known stereotypes such as male domination, rural work ethic, and freedom, the dominant ideal is enforced through the selling of these products. By utilizing American ideals and colors, the advertisements played into the American ideal of patriotism.